How Self-Perception and Parental Involvement Correlate to Enjoyment in Playing Basketball - Novrizal Achmad Novan; Masayu Rizka Risjanna; Wulandari Putri (JUARA : Jurnal Olahraga, 2022)
Psychological aspects, such as self-perception and parental involvement, are essential for child development and school-age basketball athlete achievements. This study aimed to determine the relationship between self-perception and parental involvement of the students and their enjoyment of playing basketball. The method used in this study was the quantitative method using a cross-sectional approach. This research was conducted in 2021. The population involved school-age basketball athletes aged 12 to 14 years from 6 Basketball Clubs in Bandung and the parents of the athletes involved in the training process. The Physical Self Perception Profile for Children (PSPP-C), Parental Involvement in Sport Questionnaire (PISQ), and Source of Enjoyment in Youth Sport Questionnaire (SEYSQ-H) were the three questionnaires used in this study. Bivariate analysis of this study used the chi-square test. The chi-square test showed that the self-perception variable and parental involvement variable each had indicated a significant relationship with playing enjoyment. The results showed that f = 45 (37.5%) had a poor playing enjoyment and f = 75 45 (62.5%) had a reasonable playing enjoyment. Athletes who lack self-perception and parental involvement have a higher risk of experiencing less delight in playing basketball than athletes who have good self-perceptions and parental involvement.